Visual hallucination induced by duloxetine use: a male case diagnosed with generalized anxiety disorder - Yazici, Kemal Utku; Percinel Yazici, Ipek (Taylor & Francis Ltd, 2018)
Duloxetine is a serotonin-noradrenaline reuptake inhibitor. It has been increasingly used in child and adolescent psychiatric practice in recent years. In this paper, we presented a 16-year-old male patient diagnosed with generalized anxiety disorder who had developed visual hallucinations after treatment with duloxetine. The visual hallucinations resolved after duloxetine were stopped. To the best of our knowledge, this is the first reported case from the adolescent age group who described visual hallucinations during duloxetine treatment.
Keywords: Adolescent; duloxetine; generalized anxiety disorder; visual hallucination